Active steering control research using closed-loop dynamic simulation for semi-trailer trains. Issue 4 (10th June 2022) - Zhaowen, Deng; Xinxin, Kong; Wei, Yu; Wei, Gao
To improve the lateral stability of the semi-trailer train at high speeds, the active steering control strategy for tractor and semi-trailer is proposed and examined using closed-loop dynamic simulation. A linear yaw plane model with 3-DOF of semi-trailer train is built and verified, and a directional preview driver model applied the preview-predictor follow strategy is developed and integrated with the vehicle model. The proportional feedforward, fuzzy feedback, and proportional-integral-derivative controller (PID) active steering controllers are proposed and adopted individually or in combination, the effectiveness of the active steering control strategy presented have been verified and analysed based on the driver/articulated vehicle closed-loop control system. The simulation results show that the active steering control strategy proposed has an obvious advantages over the conventional uncontrolled vehicle, effectively reducing the values of index, and improving the performance of high-speed lateral stability. The method has certain reference value for improving the active safety of articulated heavy vehicle.